1982
DOI: 10.1128/jb.150.3.1109-1114.1982
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transport system in a facultative iron-oxidizing bacterium, Thiobacillus ferrooxidans

Abstract: Properties of a heat-labile glucose transport system in Thiobacillusferrooxidans strain AP-44 were investigated with iron-grown cells. [14C]glucose was incorporated into ceil fractions, and the cells metabolized [14C]glucose to 14CO2. Amytal, rotenone, cyanide, azide, 2,4-dinitrophenol, and dicyclohexylcarbodiimide strongly inhibited [14C]glucose uptake activity, suggesting the presence of an energy-dependent glucose transport system in T. ferrooxidans. Heavy metals, such as mercury, silver, uranium, and molyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is due to the very close association between an obligately heterotrophic bacterium, Acidiphilium cryptum, and T. ferrooxidans in supposedly pure cultures (1, 4). Recently, Sugio et al (8) reported the isolation of a facultative iron-oxidizing T. ferrooxidans strain which was able to utilize glucose and grow on an organic medium without iron. However, the culture used by Sugio et al (8) has been shown to be impure and was a mixture of heterotrophic A. cryptum (70 mol% guanine plus cytosine [G+C] content) and an obligately autotrophic T. ferrooxidans (57 mol% G+C) (A. Harrison, Division of Biological Sciences, University of Missouri, Columbia, Mo., personal communication).…”
mentioning
confidence: 99%
“…This is due to the very close association between an obligately heterotrophic bacterium, Acidiphilium cryptum, and T. ferrooxidans in supposedly pure cultures (1, 4). Recently, Sugio et al (8) reported the isolation of a facultative iron-oxidizing T. ferrooxidans strain which was able to utilize glucose and grow on an organic medium without iron. However, the culture used by Sugio et al (8) has been shown to be impure and was a mixture of heterotrophic A. cryptum (70 mol% guanine plus cytosine [G+C] content) and an obligately autotrophic T. ferrooxidans (57 mol% G+C) (A. Harrison, Division of Biological Sciences, University of Missouri, Columbia, Mo., personal communication).…”
mentioning
confidence: 99%